Statewide Implementation of Universal Third-Trimester Repeat HIV Testing in Illinois - Yee, Lynn M.; Ayala, Laurie D.; Roach, Alexis M.; Statton, Anne; Randhawa, Sukhdeep; Garcia, Patricia M.; Miller, Emily S. (American Journal of Perinatology, 2023)
Objective This article aims to assess statewide uptake of HIV repeat testing in the first 2 years after the implementation of an amendment to the Illinois Perinatal HIV Prevention Act (IPHPA) mandating universal repeat HIV testing in the third trimester.Study Design This is a retrospective, population-based study of all birthing individuals in Illinois (2018–2019). Data were collected using the state-mandated closed system of perinatal HIV test reporting. We evaluated the incidence of mother–infant pairs with negative early tests and repeat third-trimester tests (RTTTs) performed in adherence with the law, as well as the timing of the performance of the RTTTs (outpatient vs. inpatient). Chi-square tests of trend by quarter were performed to ascertain sustainability.Results Of 138,805 individuals delivered in 2018, 80.6% presented with early test and RTTTs. In 2018, outpatient RTTTs improved from 71.8% (quarter 1) to 85.1% (quarter 4; p < 0.001). In 2018, the proportion of mother–infant dyads who received testing that was adherent to the IPHPA Amendment was 92.1, 95.5, 96.7, and 96.4% in quarters 1 through 4, respectively (p < 0.001). In 2019, outpatient RTTTs performance remained high (87.4%) and stable (p = 0.06). In 2019, 99.9% of mother–infant dyads had testing adherent to the mandate in quarters 1 through 4 (p = 0.39). Of individuals who presented without RTTTs, 93.5% (2018) and 98.8% (2019) underwent inpatient testing before delivery.Conclusion Implementation of RTTTs in Illinois was rapid, successful, and sustained in its first 2 years. Public health methodologies from Illinois may benefit other states implementing RTTT programs.Key Points
Keywords: HIV testing; repeat HIV testing; perinatal HIV; third-trimester HIV test; HIV seroconversion